ENIGMA’s simple seven: Recommendations to enhance the reproducibility of resting-state fMRI in traumatic brain injury - Caeyenberghs, Karen; Imms, Phoebe; Irimia, Andrei; Monti, Martin M.; Esopenko, Carrie; de Souza, Nicola L.; Dominguez D, Juan F.; Newsome, Mary R.; Dobryakova, Ekaterina; Cwiek, Andrew; Mullin, Hollie A.C.; Kim, Nicholas J.; et al. (NeuroImage clinical, 2024)
•rsfMRI has seen increased adoption recently, with 181 published studies to date.•7 recommendations to produce results that are reliable, harmonizable and reproducible.•Future directions include connectomics, lesion mapping and single-subject analyses. Resting state functional magnetic resonance imaging (rsfMRI) provides researchers and clinicians with a powerful tool to examine functional connectivity across large-scale brain networks, with ever-increasing applications to the study of neurological disorders, such as traumatic brain injury (TBI). While rsfMRI holds unparalleled promise in systems neurosciences, its acquisition and analytical methodology across research groups is variable, resulting in a literature that is challenging to integrate and interpret. The focus of this narrative review is to address the primary methodological issues including investigator decision points in the application of rsfMRI to study the consequences of TBI. As part of the ENIGMA Brain Injury working group, we have collaborated to identify a minimum set of recommendations that are designed to produce results that are reliable, harmonizable, and reproducible for the TBI imaging research community. Part one of this review provides the results of a literature search of current rsfMRI studies of TBI, highlighting key design considerations and data processing pipelines. Part two outlines seven data acquisition, processing, and analysis recommendations with the goal of maximizing study reliability and between-site comparability, while preserving investigator autonomy. Part three summarizes new directions and opportunities for future rsfMRI studies in TBI patients. The goal is to galvanize the TBI community to gain consensus for a set of rigorous and reproducible methods, and to increase analytical transparency and data sharing to address the reproducibility crisis in the field.